2021
DOI: 10.1038/s41598-021-89581-x
|View full text |Cite
|
Sign up to set email alerts
|

Low annual temperature likely prevents the Holarctic amphipod Gammarus lacustris from invading Lake Baikal

Abstract: Species with effective thermal adaptation mechanisms allowing them to thrive within a wide temperature range can benefit from climatic changes as they can displace highly specialized species. Here, we studied the adaptive capabilities of the Baikal endemic amphipods Eulimnogammarus verrucosus (Gerstfeld, 1858) and Eulimnogammarus cyaneus (Dybowsky, 1874) compared to the potential Holarctic Baikal invader Gammarus lacustris Sars, 1863 at the cellular level including the energy metabolism and the antioxidant sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Mostly inhabits the pluvial lakes of the region (Fig. 1), though it is also observed in lakes of the Baikal Rift Zone (previous indications in Baikal are accidental, in Stom & Timofeev 1999; but see Vereshchagina et al 2021). Kamaltynov (2009) reported the following data: common at depths of 0-7 m, on pebbles with sand and detritus, silted sand, flooded woods, remains of vegetation, and abundant in aquatic plant thickets.…”
Section: Distribution and Ecologymentioning
confidence: 84%
“…Mostly inhabits the pluvial lakes of the region (Fig. 1), though it is also observed in lakes of the Baikal Rift Zone (previous indications in Baikal are accidental, in Stom & Timofeev 1999; but see Vereshchagina et al 2021). Kamaltynov (2009) reported the following data: common at depths of 0-7 m, on pebbles with sand and detritus, silted sand, flooded woods, remains of vegetation, and abundant in aquatic plant thickets.…”
Section: Distribution and Ecologymentioning
confidence: 84%
“…cold adaptation, Eulimnogammarus cyaneus, Eulimnogammarus verrucosus, freshwater lake, Gammarus lacustris, Lake Baikal, transcriptome sequencing drastically reduced locomotor activity upon long-term cold exposure (Vereshchagina et al, 2021). Gammarus lacustris can be found inactive in leaf litter in winter and spring (own field observations).…”
Section: Introductionmentioning
confidence: 96%
“…Eulimnogammarus cyaneus is more thermotolerant than E. verrucosus and inhabits the upper littoral throughout the year. Field observations revealed that E. verrucosus and E. cyaneus maintain high locomotor activity at low temperatures (Vereshchagina et al, 2021) and E. verrucosus was found to reproduce during winter (Gavrilov, 1949). Gammarus lacustris has a slightly higher upper thermal limit than the Baikal endemic E. cyaneus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations